PENERAPAN PROBLEM SOLVING PADA MANAJEMEN REKRUTMEN PESERTA DIDIK BARU DI MAN 3 PESISIR SELATAN - Firmansyah, Virgo; Vadhillah, Syukra; Hasnawati, Hasnawati (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
The aim of new student recruitment management is to obtain superior students in accordance with the school's needs in educating and developing students. The type of research used is qualitative research with a descriptive approach. This research was carried out scientifically in research. This research is intended to look directly into the field regarding activities carried out scientifically. The source of information obtained comes from the actions of people who are observed or interviewed. Then the information is taken and collected one by one using language that is easy to understand and logistical. The guidelines given to new students are quite good. This is proven by the appreciation from the school principal to the committee and as the head of the madrasah he always monitors the committee's performance. The aim is to find out whether all the committees formed have written it well or not. There is a good recruitment management strategy by the committee, this can be seen from the use of digital platforms used by the committee to attract new students.